PERMO-TRIASSIC PALEOMAGNETISM OF THE NORTH PAMIR: TECTONIC IMPLICATIONS - Bazhenov M.L. (My University, 1996)
After stepwise thermal demagnetization of Upper Permian tuffaceous red beds (localities 1 and 2) and Triassic volcanics (locality 3) of North Pamir (Central Asia), the following mean directions of characteristic magnetization components were obtained: (1) Upper Permian (locality 1): D = 179.3°, I = -38.0°, alpha95 = 5.4° (29 samples); (2) Upper Permian (locality 2): D = 137.4°, I = -42.0°, alpha95 = 6.6° (20 samples); (3) Middle-Upper Triassic (locality 3): D = 226.8°, I = -63.8°, alpha95 = 4.4° (16 samples). The conglomerate and fold tests are positive for the first and third results, whereas no field test could be performed for the second one. The Late Permian locality mean inclinations are statistically indistinguishable, and the observed difference in mean declinations closely matches that in structural trends between localities 1 and 2. This constitutes a positive fold test and, at the same time, points to oroclinal bending of the Pamir structures, thus confirming an earlier conclusion about the secondary origin of this arc. Permian and Triassic paleolatitudes, together with earlier published Early Cretaceous data, fall close to the European reference inclination curve. This implies that North Pamir has been close to the Eurasia landmass at least since the Late Permian, and the major part of the India-Eurasia convergence was absorbed to the south of this zone.
Keywords: Triassic; Mesozoic::Triassic; Мезозой::Триасовая